Pattern Transactional Communication in Mashasiswa Organization in UIN Mahmud Yunus Batusangkar - Surya, Rahmad; Pratama, Reffa Amanda (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
UIN Mahmud Yunus Batusangkar is one of the colleges located in the Data Land district of Western Sumatra.It is a state university that is very attentive to technical learning to improve the quality of students who are educated there is one of the transactional methods in the student organization that is usually an external place in addition to the classroom where students exchange information to strengthen the competent students.┬á